Seasonal changes in plankton respiration and bacterial metabolism in a temperate shelf sea. (October 2019) - García-Martín, E. Elena; Daniels, Chris J.; Davidson, Keith; Davis, Clare E.; Mahaffey, Claire; Mayers, Kyle M.J.; McNeill, Sharon; Poulton, Alex J.; Purdie, Duncan A.; Tarran, Glen A.; Robinson, Carol
Highlights: Pronounced seasonality in plankton community respiration and bacterial production but not in bacterial respiration. Bacterial carbon demand independent of the amount of dissolved organic carbon produced by phytoplankton. Plankton contributed more to CO2 export to the atmosphere than to off-shelf export. Abstract: The seasonal variability of plankton metabolism indicates how much carbon is cycling within a system, as well as its capacity to store carbon or export organic matter and CO2 to the deep ocean. Seasonal variability between November 2014, April 2015 and July 2015 in plankton respiration and bacterial (Bacteria + Archaea) metabolism is reported for the upper and bottom mixing layers at two stations in the Celtic Sea, UK. Upper mixing layer (UML, >75 m in November, 41–70 m in April and ∼50 m in July) depth-integrated plankton metabolism showed strong seasonal changes with a maximum in April for plankton respiration (1.2- to 2-fold greater compared to November and July, respectively) and in July for bacterial production (2-fold greater compared to November and April). However UML depth-integrated bacterial respiration was similar in November and April and 2-fold lower in July. The greater variability in bacterial production compared to bacterial respiration drove seasonal changes in bacterial growth efficiencies, which had maximum values of 89% in July and minimum values of 5% in November. Rates of respiration and gross primary production ( 14 C-PP) also showed different seasonal patterns, resulting in seasonal changes in 14 C-PP:CRO2 ratios. In April, the system was net autotrophic ( 14 C-PP:CRO2 > 1), with a surplus of organic matter available for higher trophic levels and export, while in July balanced metabolism occurred ( 14 C-PP:CRO2 = 1) due to an increase in plankton respiration and a decrease in gross primary production. Comparison of the UML and bottom mixing layer indicated that plankton respiration and bacterial production were higher (between 4 and 8-fold and 4 and 7-fold, respectively) in the UML than below. However, the rates of bacterial respiration were not statistically different ( p  > .05) between the two mixing layers in any of the three sampled seasons. These results highlight that, contrary to previous data from shelf seas, the production of CO2 by the plankton community in the UML, which is then available to degas to the atmosphere, is greater than the respiratory production of dissolved inorganic carbon in deeper waters, which may contribute to offshore export.